Frontispiece: Surface Functionalization of g‐C3N4: Molecular‐Level Design of Noble‐Metal‐Free Hydrogen Evolution Photocatalysts. Issue 29 (13th July 2015) - Chen, Yin; Lin, Bin; Yu, Weili; Yang, Yong; Bashir, Shahid M.; Wang, Hong; Takanabe, Kazuhiro; Idriss, Hicham; Basset, Jean‐Marie
<x xml:space="preserve">Abstract</x> Photocatalysis A stable noble‐metal‐free hydrogen evolution photocatalyst based on graphitic carbon nitride (g‐C3N4) has been developed by a molecular‐level design strategy, as reported by B. Lin, K. Takanabe, H. Idriss, J.‐M. Basset et al. in their Communication on page 10290 ff. Surface functionalization is successfully conducted to introduce a single nickel active site onto the surface of the semiconducting g‐C3N4 . This catalyst family, with 0.1 wt % Ni, is found to produce hydrogen with a rate near to the value obtained by using 3 wt % platinum as co‐catalyst, and also exhibits very good stability under hydrogen evolution conditions.